2010
DOI: 10.1103/physreve.82.056326
|View full text |Cite
|
Sign up to set email alerts
|

Structures in magnetohydrodynamic turbulence: Detection and scaling

Abstract: We present a systematic analysis of statistical properties of turbulent current and vorticity structures at a given time using cluster analysis. The data stem from numerical simulations of decaying three-dimensional magnetohydrodynamic turbulence in the absence of an imposed uniform magnetic field; the magnetic Prandtl number is taken equal to unity, and we use a periodic box with grids of up to 1536³ points and with Taylor Reynolds numbers up to 1100. The initial conditions are either an X -point configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 113 publications
(109 reference statements)
8
96
1
Order By: Relevance
“…Biskamp 2003). These and other observational hallmarks of the reconnection process have been identified in extreme ultraviolet (EUV) images of the corona from Solar and Heliospheric Observatory and Solar Terrestrial Relations Observatory spacecraft (Uritsky et al 2007(Uritsky et al , 2013, flyby time-series data from MErcury Surface, Space ENvironment, GEochemistry, and Ranging probe (Uritsky et al 2011), and numerical data from high-resolution 3D simulations of prescribed, vorticity-laden MHD flows (Uritsky et al 2010b). …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Biskamp 2003). These and other observational hallmarks of the reconnection process have been identified in extreme ultraviolet (EUV) images of the corona from Solar and Heliospheric Observatory and Solar Terrestrial Relations Observatory spacecraft (Uritsky et al 2007(Uritsky et al , 2013, flyby time-series data from MErcury Surface, Space ENvironment, GEochemistry, and Ranging probe (Uritsky et al 2011), and numerical data from high-resolution 3D simulations of prescribed, vorticity-laden MHD flows (Uritsky et al 2010b). …”
Section: Introductionmentioning
confidence: 93%
“…The log-log slopes of the SFs estimated in this range serve as empirical proxies for the theoretical exponents ζ p describing the higher-order scaling of transverse v θϕ and B θϕ perturbations, as discussed in §2. The slope of the second-order SF has special significance as it yields the exponent ζ 2 directly related to the slope α = ζ 2 + 1 of the Fourier power spectrum of the fluctuations (see, e.g., Uritsky et al 2011).…”
Section: Structure Functionsmentioning
confidence: 99%
“…Instead, we start with detecting temporal traces of features in individual solar locations, and then verify their spatial adjacency. This algorithmic solution is fast and memory-efficient; see Uritsky et al (2010b) for its complete description and numerical validation. Both MDI and EUVI data sets are characterized by broad distributions of pixel values (Figure 3), encompassing more than three orders of magnitude for the magnetic field and about two orders of magnitude for the EUVI flux.…”
Section: Event Detectionmentioning
confidence: 99%
“…Recent work investigating the statistics of these coherent structures, self-consistently generated by the plasma turbulence, has demonstrated that the dissipation of turbulent energy is largely concentrated in these current sheets (Uritsky et al 2010;Osman et al 2011;Zhdankin et al 2013). Since current sheets are associated with enhanced dissipation, illuminating their origin and nature is critical to identifying the dominant physical mechanisms of dissipation in plasma turbulence.…”
Section: Introductionmentioning
confidence: 99%